2021
DOI: 10.3390/v13071346
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2/Receptor Axis in Heart and Blood Vessels: A Crisp Update on COVID-19 Disease with Cardiovascular Complications

Abstract: The SARS-CoV-2 virus causing COVID-19 disease has emerged expeditiously in the world and has been declared pandemic since March 2020, by World Health Organization (WHO). The destructive effects of SARS-CoV-2 infection are increased among the patients with pre-existing chronic conditions and, in particular, this review focuses on patients with underlying cardiovascular complications. The expression pattern and potential functions of SARS-CoV-2 binding receptors and the attributes of SARS-CoV-2 virus tropism in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 276 publications
0
11
1
Order By: Relevance
“…Various components in the blood, including macromolecules (mainly albumin and globulin), enter the alveolar cavity. This fluid in the alveolar cavity then induces aggravated dyspnea ( 35 37 ). The alveolar liquid evaporates under airflow action, leaving behind plasma proteins and necrotic alveolar epithelial debris to form a transparent membrane, leading to lung consolidation ( 3 6 , 38 , 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various components in the blood, including macromolecules (mainly albumin and globulin), enter the alveolar cavity. This fluid in the alveolar cavity then induces aggravated dyspnea ( 35 37 ). The alveolar liquid evaporates under airflow action, leaving behind plasma proteins and necrotic alveolar epithelial debris to form a transparent membrane, leading to lung consolidation ( 3 6 , 38 , 39 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mean and median age of the study participant was 47 years old. This age group is much lower than the median age group in a study participant of SARS COV-2 comorbidity network and outcome in Hospitalized patients in Crema, Italy by Tommaso Gili (40) in 2021, in which the median age group was 70.8 years of age. This difference could be accounted for by the population age distribution difference between the two countries.…”
Section: Discussionmentioning
confidence: 81%
“…The maximum case fatality rate was observed in the age category between 60-69 years of age. But in a study conducted by Tommaso Gili (40), the maximum case fatality rate was observed in the age category > 90 years of age. In a study conducted by Tommaso Gili (40), the case fatality rate in the age group 60-69 years of age was reported to be 6.6%.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, directly produced inflammatory cytokines induce genes responsible for other mediators like reactive oxygen species prostanoids, nitric oxide, leukotrienes, bradykinin, platelet activating factor causing further endothelium damage and additionally sparking this vicious cycle of vessel integrity damage. Platelet activating factor overproduction leads to easier thrombin generation and fibrin formation, which even more so with large amounts of von Willebrand factor multimers release leads to blood hypercoagulability and creates susceptibility to thrombus formation [ 23 26 ]. The dysfunctional endothelium is unable to produce NO, causing its deficiency, which is responsible for the disturbance of the vasorelaxation effect.…”
Section: Discussionmentioning
confidence: 99%